Solid Oxide Cell Degradation Operated in Fuel Cell and Electrolysis Modes: A Comparative Study on Ni Agglomeration and LSCF Destabilization. (30th May 2017) - Hubert, Maxime; Laurencin, Jérôme; Cloetens, Peter; Mougin, Julie; Ferreira Sanchez, Dario; Pylypko, Sergii; Morales, Miguel; Morata, Alex; Morel, Bertrand; Montinaro, Dario; Siebert, Elisabeth; Lefebvre-Joud, Florence
Abstract : A set of long-term tests have been carried out in fuel cell and electrolysis modes on typical Ni-YSZ//YSZ//LSCF-CGO cells. In similar operating conditions, the degradation rates were found to be higher in electrolysis than in fuel cell operation. To explain such results, both Ni agglomeration and LSCF destabilization have been investigated by coupling advanced post-test characterizations and modelling. Thanks to 3D electrode reconstructions, it has been found that Ni coarsening upon operation is not sensitive to the polarization, even if the agglomeration explains a significant part of the cell degradation. At the contrary, post-test analyses have revealed that Sr diffusion and formation of SrZrO3 at YSZ/CGO interface occur mainly during electrolysis operation, whereas the process is very limited in fuel cell mode. Therefore, the higher degradation rates measured in electrolysis mode could be related to the higher rate of LSCF demixing.